The The Perfumery Spices of Dayak Land and Its Trade in the Nineteenth Century - Listiana, Dana (Jurnal Masyarakat dan Budaya, 2022)
The study of spices in Kalimantan area tends to focus on pepper, a commodity that can be said to introduce this island as a ‘pepper country’ to the wider world in the maps made by European explorers. In fact, other commodities, such as garu (agarwood) and sintok (wild cinnamon), have also been traded long before pepper. As a commodity, the two endemic fragrances that grow naturally in the forest certainly have different effects on the community than the cultivated pepper. How the mutual influence that binds between the community and the environment in the perfume trade is the focus that will be revealed using the historical method with an environmental history approach. Thus, the environment becomes an aspect that is also discussed in changing people’s lives. This is different from the study of pepper which focuses more on the political-economic aspects. The results showed that the production and trade system of perfumery spices is engaged with the values, traditions, and rules of the local forester of Dayak as the main actors, both as individuals and groups